Changes in its Wear Resistance When Alloying Aluminum Alloys with Lithium (Texas Journal of Engineering and Technology, 2022)
The article investigated the hardness of aluminum alloys of grades AK7 and D16 according to wear resistance when applying a lithium fluoride compound as a flux, changes in abrasive wear resistance of samples. The study was conducted in the laboratory of "Foundry technologies" of the Tashkent State Technical University. Based on the results of the experiments, the authors present their conclusions in the article.